Abrasion-Induced Acceleration of Melt Crystallisation of Wet Comminuted Polybutylene Terephthalate (PBT) - Tischer, Florentin; Düsenberg, Björn; Gräser, Timo; Kaschta, Joachim; Schmidt, Jochen; Peukert, Wolfgang (Polymers, 2022)
Within this contribution, the effect of grinding media wear on the melt crystallisation of polybutylene terephthalate (PBT) is addressed. PBT was wet ground in a stirred media mill in ethanol using different grinding media beads (silica, chrome steel, cerium-stabilised and yttrium-stabilised zirconia) at comparable stress energies with the intention to use the obtained particles as feed materials for the production of feedstocks for laser powder bed fusion additive manufacturing (PBF-AM). In PBF‑AM, the feedstock’s optical, rheological and especially thermal properties—including melt crystallisation kinetics—strongly influence the processability and properties of the manufactured parts. The influence of process parameters and used grinding media during wet comminution on the optical properties, crystal structure, molar mass distribution, inorganic content (wear) and thermal properties of the obtained powders is discussed. A grinding media-dependent acceleration of the melt crystallisation could be attributed to wear particles serving as nuclei for heterogeneous crystallisation. Yttrium-stabilised zirconia grinding beads proved to be the most suitable for the production of polymer powders for the PBF process in terms of (fast) comminution kinetics, unchanged optical properties and the least accelerated crystallisation kinetics.<br
Keywords: wet comminution; stirred media mills; abrasion; polymer; additive manufacturing; powder bed fusion; thermal properties; isothermal DSC

Closed loop recycling approach for aged polyamide 12 feedstocks for powder bed fusion by precipitation from a moderate solvent combined with solvolysis - Tischer, Florentin; Cholewa, Simon; Düsenberg, Björn; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2025)
A major challenge in the powder bed fusion (PBF) process with polyamides, which are the most commonly used powders, is the handling of already used powder (aged powder). During PBF, polyamide powders undergo chemical ageing, resulting in altered thermal and rheological properties of the feedstock material. Components made from aged powder are of inferior quality. Therefore, aged powder is usually refreshed with new (virgin) powder. Although, a substantial amount of aged powder accumulates over the course of processing. These excess quantities are either employed in other plastic manufacturing processes (downcycling) or, more frequently, disposed. A combined process of solvolysis with subsequent thermally induced liquid-liquid phase separation and polymer crystallisation (TIPS+S) is used to restore the thermal properties and rheological properties of aged polyamide 12 (PA12) and thus to make the powders suitable for PBF again. The degree of solvolysis of the aged PA12 is tuned by reaction temperature or reaction time. A kinetic model allows to determine suitable process parameters for TIPS+S depending on the ageing condition of the feed to match the thermal properties of the recycled PA12 powders to those of PA12 virgin powder. The optimised recycled PA12 powder shows comparable zero shear viscosity, particle size distribution, particle shape and flowability to the virgin material. Specimen built from equally mixed recycled and aged PA12 powder achieved the same mechanical properties like those obtain by PBF of equally mixed virgin and aged powder. Therefore, a closed loop recycling approach is feasible, in which aged PA12 powders from the PBF process are recycled by the proposed TIPS+S proces
Keywords: Polyamide 12; Polymer recycling; Powder bed fusion; Powder characterisation

Control of Crystallization of PBT-PC Blends by Anisotropic SiO2 and GeO2 Glass Flakes - Düsenberg, Björn; Esper, Julian Duane; Maussner, Felix; Mayerhofer, Magdalena; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Polymer composites and blend systems are of increasing importance, due to the combination of unique and different material properties. Blending polybutylene terephthalate (PBT) with polycarbonate (PC) has been the focus of attention for some time in order to combine thermo-chemical with mechanical resistance. The right compounding of the two polymers is a particular challenge, since phase boundaries between PBT and PC lead to coalescence during melting, and thus to unwanted segregation within the composite material. Amorphization of the semi-crystalline PBT would significantly improve the blending of the two polymers, which is why specific miscibility aids are needed for this purpose. Recent research has focused on the functionalization of polymers with shape-anisotropic glass particles. The advantage of those results from their two-dimensional shape, which not only improves the mechanical properties but are also suspected to act as miscibility aids, as they could catalyze transesterification or act as crystallization modifier. This work presents a process route for the production of PBT-PC blends via co-comminution and an in-situ additivation of the polymer blend particles with anisotropic glass flakes to adjust the crystallinity and therefore enhance the miscibility of the polymers.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anisotropic particles; co-comminution; crystallization modifiers; functional filler; glass flakes; polymer-blends

Enabling triboelectric charging as a powder charging method for electrophotographic powder application in laser-based powder bed fusion of polymers by triboelectric charge control - Kopp, Sebastian-Paul; Düsenberg, Björn; Eshun, Pius Marcellinus; Schmidt, Jochen; Bück, Andreas; Roth, Stephan; Schmidt, Michael (Additive Manufacturing, 2023)
Substituting conventional doctor blade- or roller-based powder application methods for laser-based powder bed fusion of polymers (PBF-LB/P) by electrophotographic powder application (EPA) offers significant advantages. In particular, the selective powder deposition enabled by EPA allows high powder efficiency and the possibility to locally adjust part properties during their fabrication. However, defined charging of powder particles is crucial for achieving an accurate selective deposition of powder layers by means of electrophotography. This is the first comprehensive study on the specific triboelectric charge control of polymer particles for their subsequent use in electrophotographic powder application for PBF-LB/P. For this purpose, approaches for charge control of toner particles in the context of digital (2D) printing technologies are adapted and applied to polypropylene (PP) feedstocks for PBF-LB/P. In order to show transferability to other polymers, the charge control method developed in this paper is also applied to polyamide 12 (PA12) high density polyethylene (HDPE) and polystyrene (PS). For successful EPA, unipolar charging of polymer particles is crucial. However, non-functionalized PP shows a strongly bipolar triboelectric charging, which is unsuitable for EPA. The charge control method developed in this work shifts this strongly bipolar triboelectric charging to a unipolar charging. This is achieved by the synergy of both functionalizing the particle surface with charge control agents (CCAs) and choosing suitable carrier particles known from two-component toners. The developed method allows to control crucial parameters of triboelectric charging, namely polarity, amount of charge and resulting surface potential. Furthermore, the presented results provide new insights into the transfer behavior of charged PP particles in an external electric field. Finally, this enables the triboelectric charging mechanism to be used for electrophotographic powder application in PBF-LB/P.<br
Keywords: Charge control Electrophotography Triboelectric charging Laser powder bed fusion Polymer particles Powder application

Enhancing Photoelectric Powder Deposition of Polymers by Charge Control Substances - Düsenberg, Björn; Kopp, Sebastian-Paul; Tischer, Florentin; Schrüfer, Stefan; Roth, Stephan; Schmidt, Jochen; Schmidt, Michael; Schubert, Dirk W.; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Charge control substances (CCS) as additives for polymer powders are investigated to make polymer powders suitable for the electrophotographic powder deposition in powder-based additive manufacturing. The use of CCS unifies the occurring charge of a powder, which is crucial for this novel deposition method. Therefore, commercially available polymer powder is functionalized via dry coating in a shaker mixer with two different CCS and analyzed afterwards. The flowability and the degree of coverage of additives on the surface are used to evaluate the coating process. The thermal properties are analyzed by use of differential scanning calorimetry. Most important, the influence of the CCS on the powder charge is shown by measurements of the electrostatic surface potential at first and the powder deposition itself is performed and analyzed with selected formulations afterwards to show the potential of this method. Finally, tensile strength specimens are produced with the conventional deposition method in order to show the usability of the CCS for current machines.<br
Keywords: additive manufacturing; charge control substances; photoelectric powder deposition; polypropylene; dry coating

Flowability of plant based food powders: Almond, chestnut, chickpea, coconut, hazelnut and rice - Düsenberg, Björn; Schmidt, Jochen; Sensoy, Ikay; Bück, Andreas (Journal of Food Engineering, 2023)
This study presents bulk material characterization, especially powder flowability, of eight food powders from six different plants (almond, chestnut, chickpea, coconut, hazelnut and rice). The characterization of the bulk powders includes the particle size distributions, true densities, bulk and tapped densities, as well as the powder porosity and moisture content. The flowability is determined by means of Hausner ratio, Carr's index, flow function by an annular shear cell and dynamic angle of repose. The flowability characteristics are discussed in regard to the bulk powder properties and evaluated for their applicability as some methods could give misleading results for the flowabilit
Keywords: Grains and nuts; Bulk characterization; Powder properties; Powder flowability

Formulation of hetero-aggregates in opposed jet fluidized beds - Favaro Nascimento, Raul; Men, Jialin; Düsenberg, Björn; Schmidt, Jochen; Bück, Andreas (Powder Technology, 2025)
Nanoparticle powders produced by mixing have applications in catalysis, coatings, and advanced materials, yet they remain challenging owing to the strong cohesive behavior of the constituents. Hetero-aggregates form through hetero-contacts at interfaces between chemically distinct materials, but achieving a uniform distribution of components requires an efficient mixing process. Opposed jet fluidized beds offer a promising approach for overcoming these limitations. In this study, the formulation of titania-zirconia hetero-aggregates was investigated by analyzing process parameters and their impact on the inter- and intra-aggregate mixing quality. The effects of feed composition mass ratios (1:1, 2:1, and 1:2), back pressures of the Laval nozzles (0.5, 2.5, and 5.0 bar), and processing times (1 and 5 min) were evaluated by mapping the Ti atomic fraction. The composition and shape of the hetero-aggregates were investigated. The hetero-aggregates exhibited compositions closely aligned with the expected values, based on the initial masses of the components. Shape analysis revealed star-like, elongated, and irregular structures, with circularity and roundness values of approximately 0.4 and 0.5, respectively. Most hetero-aggregates exhibited porosities between 0.971 and 0.991, indicating highly porous structures with significant void spaces. These findings demonstrate that opposed jet fluidized beds enable control over the composition and morphology of hetero-aggregates, leading to efficient nanoparticle mixing.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Aggregation; Fluidization; Mixing; Nanoparticles

Improvement of polymer properties for powder bed fusion by combining in situ PECVD nanoparticle synthesis and dry coating - Gomez Bonilla, Juan Sebastian; Düsenberg, Björn; Lanyi, Franz; Schmuki, Patrik; Schubert, Dirk W.; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Plasma Processes and Polymers, 2021)
Polypropylene (PP) powders are coated with silica nanoparticles in a fluidized bed to improve the flow behavior of the powders and the processability in powder bed fusion. The nanoparticles are produced in situ via dusty plasma‐enhanced chemical vapor deposition (PECVD) in an atmospheric‐pressure Ar/O2 plasma jet fixed at the distributor plate of the fluidized bed. Hexamethyldisiloxane is used as a precursor of the nanoparticles. The influence of the oxygen concentration in the plasma gas and the number of treatment cycles on the chemical composition of the nanoparticles, the amount of nanoparticles deposited, and the flow properties of the coated PP powders is investigated. The chemical composition of the formed silica particles is determined by X‐ray photon spectroscopy and infrared spectroscopy. The results reveal that the composition of the nanoparticles is SiOxCy, that is, the portion of organic residues introduced by the precursor can be controlled by changing the oxygen concentration in the plasma gas. The mass of nanoparticles deposited on the polymer powder's surface, as determined by inductively coupled optical emission spectroscopy, shows a linear dependence of the number of cycles and the oxygen concentration in the plasma gas. A considerable improvement of the flow behavior of the PP powders is observed after PECVD treatment.<br
Keywords: nanocomposites; particle coating; plasma‐enhanced chemical vapor deposition; powder bed fusion; powder flowability

Magnetic polyamide 11 powder for the powder bed fusion process by liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Groppe, Philipp; Granath, Tim; Düsenberg, Björn; Mandel, Karl; Drummer, Dietmar; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (Additive Manufacturing, 2024)
Herein, we demonstrate the preparation of magnetic polyamide 11 feedstock powders for powder bed fusion (PBF) using liquid-liquid phase separation and crystallization. By adding magnetic nanomaterials during the precipitation process, the particulate additive is incorporated into the polymer matrix. This enables the production of filled systems at single particle level, which is advantageous in terms of the adjustable magnetic strength and homogeneity of the powder. Thermogravimetric analysis is used to determine the additive content and onset temperature of decomposition of composite powders, where additive-enhancement of PA11 powders with magnetic iron oxide nanoparticles showed a positive influence on the thermal stability of the feedstock. Successive analysis of particle size distribution, shape, colour, crystal structure, magnetic properties and thermal properties of the composite powders are carried out and their properties are discussed with respect to the PBF process. A decrease in particle size, width of the thermal process window and isothermal crystallization time can be attributed to the nucleating effect of the magnetic additive. The PBF processability of the composite feedstock is demonstrated by the production of magnetic tensile bar specimens from additive-enhanced PA11 powders with 1 wt.-% magnetic iron oxide.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Magnets; Nanocomposites; Polymer precipitation; Powder bed fusion; Powder characterization

Magnetizing Polymer Particles with a Solvent-Free Single Stage Process Using Superparamagnetic Iron Oxide Nanoparticles (SPION)s - Düsenberg, Björn; Groppe, Philipp; Müssig, Stephan; Schmidt, Jochen; Bück, Andreas (Polymers, 2022)
Magnetic polymer composites are used in a variety of applications in many industries. Their production methods are usually time-consuming and solvent-intensive as they are performed in liquid phase processes, such as emulsion polymerization or precipitation. In this work, a quick, easy, and solvent-free method is presented to coat polymer particles with a discrete, non-coherent coating of superparamagnetic nanoparticles. The results of the dry coating process are evaluated optically, by means of scanning electron microscopy (SEM), via powder X-ray diffraction and thermally by means of differential scanning calorimetry, before finally demonstrating the effectiveness of dry coating by means of a vibrating sample magnetometer<br

Polyamide 11 nanocomposite feedstocks for powder bed fusion via liquid-liquid phase separation and crystallization - Tischer, Florentin; Cholewa, Simon; Düsenberg, Björn; Drummer, Dietmar; Peukert, Wolfgang; Schmidt, Jochen (Powder Technology, 2023)
Within this contribution, the incorporation of nanoparticles (SiO2, Al2O3, TiO2) into the matrix of precipitated polyamide particles during thermally induced phase separation (TIPS) is demonstrated. The obtained polymer composite powders are tailored for their application in powder bed fusion (PBF). The flexible process allows to tune and adapt the powder properties to meet specific challenges like narrow particle size distribution, spherical particles, high additive contents and good distribution of the additive within the powder. Thermogravimetric analysis and electron microscopy prove the incorporation of the nano-sized additive into the matrix of the polymer. The influence of the additive material during polymer precipitation on the particle size distribution and shape of the powders is discussed. Thermal properties of the composite powders were assessed by dynamic and isothermal DSC for subsequent Avrami analysis. The observed acceleration of the crystallization kinetics could be attributed to the nucleating effect of the additive. All powders showed an easy-flowing (flow index ffC > 4) behavior. This allowed the deposition of homogeneous powder layers during PBF experiments also at high temperatures. The processability of the composite powders in the PBF process was demonstrated by single layer experiments.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Liquid-liquid phase separation; Nanocomposite; Polyamides; Polymer precipitation; Powder bed fusion; Tailoring bulk properties; Thermal analysis

Poly(butylene terephthalate) for Laser Powder Bed Fusion of Polymers: Feedstock Precipitation and Powder Characterization - Tischer, Florentin; Düsenberg, Björn; Kaschta, Joachim; Bück, Andreas; Peukert, Wolfgang; Schmidt, Jochen (ACS Applied Polymer Materials, 2024)
Powder bed fusion of polymers with a laser beam (PBF-LB/P) is a layer-based additive manufacturing method that excels in producing functional components of complex geometries. However, the limitation of commercially available materials to mostly polyamides reduces the range of applications for PBF-LB/P-processed parts. Recently, liquid−liquid phase separation and crystallization have been reported as a suitable method to produce poly(butylene terephthalate) (PBT) microparticles of good flowability as a PBF-LB/P feedstock. PBT is an interesting plastic feedstock as its properties allow for an extension of the application of AM-built parts in the automotive and electronics sectors. Starting from PBT feed materials with different molar mass distributions, we investigate the effect of the feed material used in the thermal precipitation process under otherwise identical process parameters on the resulting PBT powder properties. The thermal precipitation process is highly robust with respect to bulk solid properties, such as particle size distribution, particle shape, flowability, and intrinsic properties (crystal structure and melting behavior). These product characteristics are virtually unaffected by the average molar mass of the PBT feed. Melt crystallization is accelerated, while the viscosity decreases with decreasing molecular mass. Once favorable process conditions are defined, which lead to powders with suitable properties, the crystallization kinetics and melt viscosity can be adjusted accordingly without changing the powder properties. Key parameters, which influence part porosity (through melt coalescence), layer adhesion, or the tendency of the material to warp during the PBF-LB/P process, are adjustable to produce a customized starting materia
Keywords: powder characterization; powder production; poly(butylene terephthalate); powder bed fusion; liquid−liquid phase separation

Production and analysis of electrically conductive polymer – Carbon-black composites for powder based Additive Manufacturing - Düsenberg, Björn; Tischer, Florentin; Seidel, Anne Marie; Kopp, Sebastian-Paul; Schmidt, Jochen; Roth, Stephan; Peukert, Wolfgang; Bück, Andreas (Procedia CIRP, 2022)
In laser powder bed fusion, micro-particles are selectively fused by a laser to produce parts, layer-by-layer. While this process offers a high freedom of design, the variety of commercially available materials, especially composites are limited. Conductive polymers blends, are very interesting for many applications, especially as sensors with freely definable shape. First, the amount of carbon-black needed to make the composite electrically conductive has to be determined; this limit is called percolation threshold (PT). The PT depends on many properties, such as particle size and shape of both polymer and carbon-black and will be determined experimentally. In this work, polypropylene is dry mixed with different types of micron sized carbon blacks. The PT and the conductivity is determined by means of impedance spectroscopy. Finally, layers are printed to evaluate the processability of the new composite.<br
Keywords: polypropylene; carbon black; percolation threshold

Production of PBT/PC multi-material particles via a combination of co-grinding and spray-agglomeration for powder bed fusion - Riedel, Florentin; Düsenberg, Björn; Schmidt, Jochen; Bück, Andreas; Peukert, Wolfgang (Procedia CIRP, 2020)
Polybutylene terephthalate (PBT) – polycarbonate (PC) multi-materials with a PBT mass content of 25% to 75% were produced for the powder bed fusion process by the means of co-grinding and spray agglomeration. The influence of the PC content and the process parameters on the thermal properties of the obtained powders are discussed in detail. Compared to pure PBT powder, the PBT/PC multi-materials crystallize at lower temperatures, which improves the handling during the additive manufacturing proces
Keywords: multi-material particles; polycarbonate; polybutylene terephthalate; comminution; spray agglomeration

Production of spherical ester wax powders by melt emulsification for Additive Manufacturing - Tischer, Florentin; Düsenberg, Björn; Peukert, Wolfgang; Schmidt, Jochen (Procedia CIRP, 2022)
Powder bed fusion of polymers with laser beam (PBF-LB/P) involves selectively melting plastic micro particles with a laser and building up the parts layer by layer, which offers great freedom of design. However, the choice of commercially available thermoplast feedstock powders is limited (90% polyamides). In order to extend the range of materials, this contribution presents the production of highly spherical micro particles by melt emulsification followed by spray agglomeration for ester wax. The effect of process parameters during emulsification (energy input, surfactant to polymer ratio) on the particle size distribution is demonstrated in detail for the ester wax system. In order to generate and tune particle sizes to a range suitable for PBF, melt emulsified ester wax dispersions are spray agglomerated. Agglomerated ester wax powders were used for the PBF process to manufacture tensile strength specimens type 5A.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Additive manufacturing; ester wax; Polycaprolactone; Melt emulsification; Polymers; Spray agglomeration

Spray agglomeration of polymer particles: Influence of spray parameters on shape factors - Düsenberg, Björn; Schmidt, Jochen; Singh, Abhinandan Kumar; Bück, Andreas (Powder Technology, 2023)
This work systematically investigates the influence of spray parameters on the shape factor descriptors and the fractal dimensions of polymer agglomerates produced by fluidised bed spray agglomeration. Polystyrene primary-particles with sizes <100 μm (Geldart C/A) are used to investigate the shape formation during the agglomeration process with regard to the spray-parameters, i.e., volume flows of the atomization gas and the binder liquid. As binding agent, a solution of polymethyl-methacrylate in acetone is used. Analysis of the agglomerates is carried out using scanning electron microscopy and laser diffraction. Development of agglomerate-size and the distributions of the shape factors circularity, roundness and compactness are monitored by image analysis and correlated with the spray parameters. The calculation of the fractal dimensions with regard to the Sauter mean diameter using the box counting method is performed and compared with the shape factors, resulting in two complementary methods to describe the shape of agglomerates.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Fluidized bed; Fractal dimensions; Shape factor; Spray agglomeration

Temperature influence on the triboelectric powder charging during dry coating of polypropylene with nanosilica particles - Düsenberg, Björn; Tischer, Florentin; Valayne, Erika; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Powder Technology, 2022)
The influence of process temperature on the triboelectric charge during dry coating of cohesive polymer powders is investigated. The purpose of heating is to decrease the surface moisture of the powder, which results in an increase of electrical charge of the powder. The effect of the hydrophilicity of the SiO2 guest particles on the quality of the dry coating of PP host particles was investigated with respect to the integral charge of the dry coated powder. Furthermore, the flowability, crystallization behavior and degree of coverage (DOC) were investigated to determine the influence of the increased charge on these topics. Increased process temperature increases the electrical charge of the powder, which leads to a higher DOC with guest particles and, thus, drastically improved flowability compared to dry coating at ambient temperature. Furthermore, changes in the crystallization behavior of polypropylene are observed, due to more nuclei.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Crystallization; Dry coating; Flowability; Mixing; Polymer; Thermal treatment; Triboelectricity